Clinical analysis of pneumonectomy for destroyed lung: a retrospective study of 32 patients - (:unkn) unknown (SPRINGER JAPAN KK, 2019)
ObjectiveDestroyed lung is whole lung destruction secondary to chronic or recurrent lung infections. This clinical condition can result in irreversible changes in the lung parenchyma. In this study, we aimed to evaluate patients undergoing pneumonectomy with a diagnosis of lung destruction in terms of surgical technique, post-operative morbidity and mortality, and long-term outcomes.MethodsA total of 32 patients that underwent pneumonectomy due to a destroyed lung between 2005 and 2017 were retrospectively reviewed. Age, gender, presenting symptoms, etiologies, localization of the destruction, pre-operative medical history, pre- and post-operative respiratory function tests, intraoperative complications and bleeding volume, morbidity and mortality, length of hospital stay, and long-term follow-up outcomes were reviewed for each patient.ResultsThe study included 32 patients with a mean age of 31.710.8years. All the patients presented with persistent cough, whereas sputum production was presented by 25, hemoptysis by 18, and chest pain by 11 patients. The underlying primary diseases included nonspecific bronchiectasis in 20 (62.5%), tuberculosis in 9 (28.1%), left pulmonary hypoplasia accompanied by Bochdalek hernia in 2 (6.2%), and aspiration of a foreign body lodged in the left main bronchus in 1 (3.1%) patient. Mean operative time was 220.6 +/- 40.2min and mean perioperative bleeding was 450.9 +/- 225.7ml. Post-operative complications occurred in 14.2% of the patients, most commonly including atelectasis associated with stasis of secretions and wound site infection. Mean post-operative hospital stay was 11.8 +/- 2.8days and mean follow-up period was 35.5 +/- 28.3months. A significant clinical improvement was observed in 81.2% of the patients post-operatively.Conclusions Favorable long-term outcomes were obtained in our patients through careful patient selection and appropriate pre-operative work-up and surgical technique.
Keywords: Bronchiectasia; Destroyed lung; Pneumonectomy; Comfort of life; SURGICAL-TREATMENT; MORTALITY; MORBIDITY; CHILDREN